"Галич – другий Київ": середньовічна формула чи історіографічна метафора? - Ричка, В.М. (Український історичний журнал, 2006)
В основу статті покладено доповідь, виголошену автором на VI Міжнародному конгресі українців, який відбувся 28 червня – 1 липня 2005 р. в Донецьку. Здійснено спробу з’ясувати ідейний зміст та історичну реальність формули "Галич – другий Київ". The report is put at the heart of the article, which was proclaimed by the author on the 6th International congress of Ukrainianists that took place on the 28th of June – 1st of July 2005 in Donetsk. The author makes an attempt to find out the ideological content and historical reality of the formula “Halych – second Kyiv”.